2015
DOI: 10.1371/journal.pone.0124307
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell Derived Macrophages as a Cellular System to Study Salmonella and Other Pathogens

Abstract: A number of pathogens, including several human-restricted organisms, persist and replicate within macrophages (Mφs) as a key step in pathogenesis. The mechanisms underpinning such host-restricted intracellular adaptations are poorly understood, in part, due to a lack of appropriate model systems. Here we explore the potential of human induced pluripotent stem cell derived macrophages (iPSDMs) to study such pathogen interactions. We show iPSDMs express a panel of established Mφ-specific markers, produce cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
(33 reference statements)
4
41
0
Order By: Relevance
“…It has been suggested that the differentiation efficiency and yield are higher when using serum free media to differentiate EBs into myeloid precursors as opposed to serum-containing media. 26 Monolayer-directed differentiation as opposed to an EB-based differentiation that generates cells of all three germ layers may have advantage for differentiation in defined conditions, 21 but direct comparison has not been performed. Novel protocols to differentiate iPSCs to tissue resident macrophages, e.g.…”
Section: Generation Functional Feature and Molecular Profiling Of Ipsdmmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the differentiation efficiency and yield are higher when using serum free media to differentiate EBs into myeloid precursors as opposed to serum-containing media. 26 Monolayer-directed differentiation as opposed to an EB-based differentiation that generates cells of all three germ layers may have advantage for differentiation in defined conditions, 21 but direct comparison has not been performed. Novel protocols to differentiate iPSCs to tissue resident macrophages, e.g.…”
Section: Generation Functional Feature and Molecular Profiling Of Ipsdmmentioning
confidence: 99%
“…14, 33 IPSDM also serves as a powerful tool to study macrophage host-pathogen interaction. IPSDM can be infected with various strains of HIV-1, 34 and support Salmonella 26 and Chlamydia infection. 35 Knockout of IRF5/IL10RA by CRIPSR/Cas9 led to increased susceptibility to Chlamydia trachomatis infection in IPSDM.…”
Section: Disease Modeling and Functional Genomic Analyses With Ipsdmmentioning
confidence: 99%
“…These cells retain their original genetic architecture, able to self-renew and differentiate into virtually any cell types in the presence of optimal conditions. Recently, our group and others have developed methods to differentiate hiPSCs into macrophage-like cells that share characteristics of primary human macrophages and overcome some of the limitations of the existing models in human macrophage biology [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, large numbers of iPSCs from healthy donors have been differentiated into macrophages to study how common genetic variation influences innate immune responses to pathogens. Furthermore, iPSC-derived macrophages are especially useful to study human-adapted pathogens for which currently no animal models are available [8,19]. In a more translational context, proof-of-principle evidence is now emerging that iPSC-derived macrophages can be potentially exploited to treat certain types of cancer by cellular therapy [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation